High-strength and high-barrier polylactic acid film as well as preparation method and application thereof

By blending block copolymerized polylactic acid with polylactic acid matrix, the rapid crystallization and high crystallinity of polylactic acid are promoted, and the problems of slow crystallization speed and poor mechanical properties are solved, and the preparation of high-strength and high-barrier polylactic acid films are realized. In the fields of packaging and agricultural mulching.

CN119431844APending Publication Date: 2025-02-14SICHUAN UNIV
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411588508.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The crystallization rate of polylactic acid is slow, has low crystallinity and poor mechanical properties, which limits its widespread application in industry. Existing nucleating agents have problems such as poor compatibility, large dosage or biotoxicity, and it is difficult to effectively improve the crystallinity and performance of polylactic acid.

Method used

Block copolymerized polylactic acid is used as a nucleating agent and isothermal crystallization. By adjusting the amount of block copolymerized polylactic acid added and isothermal crystallization time, it promotes rapid crystallization of polylactic acid matrix, improves crystallinity, and imparts polylactic acid films. High barrier performance.

Benefits of technology

It realizes rapid crystallization and high crystallinity of polylactic acid matrix, improves the mechanical properties and high barrier properties of polylactic acid films, solves the compatibility and toxicity problems of existing nucleating agents, and is suitable for packaging and agricultural mulching films and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431844A_ABST
    Figure CN119431844A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-barrier polylactic acid film and a preparation method and application thereof.The preparation method comprises the following steps that S1, a polylactic acid matrix and block copolymerized polylactic acid are dissolved with a solvent and then mixed, and a solution is obtained; s2, precipitating the solution with ethanol to obtain a precipitate; s3, the precipitate is dried, and a blend is obtained; and S4, carrying out melting, hot pressing and isothermal crystallization on the blend to obtain the high-strength and high-barrier polylactic acid film. Block copolymerized polylactic acid is utilized to promote rapid crystallization of a polylactic acid matrix, and the polylactic acid film is endowed with high barrier property while the mechanical property of the polylactic acid film is improved. The prepared high-strength and high-barrier polylactic acid film is applied to the field of packaging or agricultural mulching films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-strength and high-barrier polylactic acid film and a preparation method and application thereof. Background Art

[0002] Polylactic acid is a biodegradable plastic with the most research value and application potential, which is synthesized from lactic acid fermented from bio-based starch. The final products of its degradation are CO2 and H2O, which can be absorbed by plant photosynthesis and are green and environmentally friendly. Polylactic acid has good mechanical properties, biocompatibility and non-toxic properties, and has broad application prospects in the fields of medicine and packaging. However, polylactic acid has a slow crystallization rate, low crystallinity, and poor mechanical properties, which severely limits its wide application in many industries.

[0003] Adding a nucleating agent to polylactic acid to reduce the nucleation barrier of polylactic acid and promote the crystallization of polylactic acid is currently the simplest and most efficient method to improve the crystallinity and performance of polylactic acid. Patents CN103804864A and CN113429768B both disclose an amide organic nucleating agent, which achieves rapid crystallization of polylactic acid. Patent CN114507425B discloses a polylactic acid nucleating agent prepared from mandelic acid and metal carboxylates, which can effectively improve the crystallization rate and crystallinity of polylactic acid, while enhancing the heat resistance of polylactic acid. Patent CN113025014A discloses a polyhydroxy compound polylactic acid nucleating agent, which can simultaneously improve the crystallization temperature, crystallinity, and crystallization rate of polylactic acid. Patents CN113502041A and CN113583407B disclose a nucleating agent containing phosphate and carboxylate respectively, which can reduce the interfacial free energy required for the crystallization nucleation of polylactic acid, thereby achieving the purpose of improving the crystallization rate and crystallinity of polylactic acid. Patent CN110016133B discloses a macromolecular nucleating agent for rapid crystallization of polylactic acid composed of a thioether and aliphatic main chain structure and an ester side chain structure. The macromolecular nucleating agent can greatly improve the crystallization rate of polylactic acid on the basis of a small amount of addition. Although the above-mentioned polylactic acid nucleating agents that have been studied can significantly improve the crystallization behavior of polylactic acid, increase the crystallization rate and crystallinity, they all have different defects. The literature Int. J. Biol. Macromol., 233 (2023), 123581 and Journal of Biotechnology, 32 (2016), 798-806 reviewed the polylactic acid nucleating agents that have been studied so far. Inorganic nucleating agents have the problems of poor compatibility with polylactic acid and large dosage. Although organic nucleating agents can be well dispersed in the polylactic acid matrix to promote heterogeneous nucleation of polylactic acid, most organic nucleating agents are biotoxic and do not meet the current requirements of green environmental protection. The molecular structure of polymer nucleating agents is difficult to control, and the mechanism of action is relatively complex, which is not conducive to the controllable regulation of polylactic acid crystallization and performance. Summary of the invention

[0004] In view of the above problems, the present invention aims to provide a high-strength and high-barrier polylactic acid film and its preparation method and application. Focusing on polylactic acid itself, a simple and easy method is used to induce rapid crystallization of the polylactic acid matrix with block copolymer polylactic acid, thereby improving the crystallinity, and giving the polylactic acid film high barrier properties while improving the mechanical properties. Block copolymer polylactic acid is green and environmentally friendly and has good compatibility with the polylactic acid matrix. The crystallinity and barrier properties of polylactic acid can be easily controlled by adjusting the addition amount of block copolymer polylactic acid and the isothermal crystallization time. The high-strength and high-barrier polylactic acid film can be used in the field of packaging or agricultural mulch.

[0005] The technical solution of the present invention is as follows:

[0006] On the one hand, a method for preparing a high-strength and high-barrier polylactic acid film is provided, comprising the following steps:

[0007] S1: using a solvent to dissolve the polylactic acid matrix and the block copolymer polylactic acid respectively, and then mixing them to obtain a solution;

[0008] S2: precipitating the solution through ethanol to obtain a precipitate;

[0009] S3: drying the precipitate to obtain a blend;

[0010] S4: melting, hot pressing and isothermal crystallization of the blend to obtain the high-strength and high-barrier polylactic acid film.

[0011] Furthermore, in step S1, the solvent is dichloromethane and / or hexafluoroisopropanol.

[0012] Furthermore, in step S1, the polylactic acid matrix is ​​left-handed polylactic acid or right-handed polylactic acid.

[0013] Furthermore, in step S1, the average molecular weight M of the polylactic acid matrix is n Greater than or equal to 8×10 4 g / mol and less than or equal to 18×10 4 g / mol, and the polydispersity index PDI is greater than 1 and less than 2.

[0014] Furthermore, in step S1, the block copolymerized polylactic acid is PLLA m -b-PDLA m or PDLA m -b-PLLA m , where 50≤m≤200, and m is the degree of polymerization.

[0015] Furthermore, in step S1, the block copolymerized polylactic acid accounts for 1-5% of the total mass of the polylactic acid matrix and the block copolymerized polylactic acid in terms of mass percentage.

[0016] Furthermore, in step S4, the melting temperature is 230-240°C, the melting time is 4-5min; the hot pressing pressure is 20MPa, and the hot pressing time is 2-3min; the isothermal crystallization temperature is 120°C, the isothermal crystallization pressure is 15-20MPa, and the isothermal crystallization time is 0-30min.

[0017] On the other hand, a high-strength and high-barrier polylactic acid film prepared by any of the above-mentioned methods for preparing a high-strength and high-barrier polylactic acid film and its application in the field of packaging or agricultural mulch film are also provided.

[0018] The beneficial effects of the present invention are:

[0019] The present invention focuses on polylactic acid itself, and uses a simple and easy method to use block copolymer polylactic acid as a nucleating agent, which is physically blended with a polylactic acid matrix, effectively promoting rapid crystallization of the polylactic acid matrix, improving crystallinity, and giving the polylactic acid film high barrier properties while improving mechanical properties. It not only solves the problem of poor compatibility between inorganic nucleating agents and polylactic acid and large dosage, but also solves the problem that other organic nucleating agents are toxic and do not meet green environmental protection requirements. It not only gives polylactic acid high barrier properties, but also maintains the original mechanical properties of polylactic acid. The present invention is conducive to promoting the wide application of polylactic acid in the field of packaging or agricultural mulch. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the technical description will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creativity and labor.

[0021] Figure 1 It is a schematic diagram of the structure of the high-strength and high-barrier polylactic acid film of the present invention.

[0022] Figure 2 These are photos of the crystallization process of the PDLA, PDLA / LD50-1%, PDLA / LD50-3% and PDLA / LD50-5% films of Example 1 under a polarizing microscope.

[0023] Figure 3 The oxygen barrier properties of the PLLA, PLLA / LD100-1%, PLLA / LD100-3% and PLLA / LD100-5% films of Example 2 at different crystallinity levels.

[0024] Figure 4 The water vapor barrier properties of the PLLA, PLLA / LD100-1%, PLLA / LD100-3% and PLLA / LD100-5% films of Example 2 at different crystallinity levels.

[0025] Figure 5 1 and 2 are stress-strain curves of the PLLA, PLLA / DL200-1%, PLLA / DL200-3% and PLLA / DL200-5% films of Example 3 when they are amorphous.

[0026] Figure 6 The stress-strain curves of the PLLA, PLLA / DL200-1%, PLLA / DL200-3% and PLLA / DL200-5% films of Example 3 at 30 min of isothermal crystallization.

[0027] Figure 7 The crystallinity changes of PLLA and its blend films (Example 4) and PDLA and its blend films (Example 5-Example 6) at different isothermal crystallization times. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0029] In one aspect, the present invention provides a method for preparing a high-strength and high-barrier polylactic acid film, comprising the following steps:

[0030] S1: using a solvent to dissolve the polylactic acid matrix and the block copolymer polylactic acid respectively, and then mixing them to obtain a solution.

[0031] In a specific embodiment, the solvent is dichloromethane and / or hexafluoroisopropanol. It should be noted that, in addition to the solvents selected in this embodiment, other good solvents for polylactic acid in the prior art can also be applied to the present invention, such as chloroform. It should be noted that although chloroform is a commonly used good solvent for polylactic acid, it is highly toxic and is a controlled solvent that is easy to make drugs, so safety should be paid attention to when using it.

[0032] In a specific embodiment, the polylactic acid matrix is ​​L-polylactic acid or D-polylactic acid. Optionally, the average molecular weight M of the polylactic acid matrix is nGreater than or equal to 8×10 4 g / mol and less than or equal to 18×10 4 g / mol, and the polydispersity index PDI is greater than 1 and less than 2.

[0033] In a specific embodiment, the block copolymer polylactic acid is PLLA m -b-PDLA m or PDLA m -b-PLLA m , where 50≤m≤200, and m is the degree of polymerization.

[0034] It should be noted that the use of the block copolymer polylactic acid can achieve rapid crystallization of the polylactic acid matrix with only a small amount of addition; when the degree of polymerization is less than 50, more block copolymer polylactic acid needs to be added to achieve rapid crystallization of the polylactic acid matrix; when the degree of polymerization is greater than 200, the molecular weight of the block copolymer polylactic acid is high, and the molecular chain movement is difficult at this time, which will be unfavorable for the rapid crystallization of the polylactic acid matrix.

[0035] In a specific embodiment, the block copolymer polylactic acid accounts for 1-5% of the total mass of the polylactic acid matrix and the block copolymer polylactic acid, in terms of mass percentage.

[0036] S2: The solution is precipitated by ethanol to obtain a precipitate.

[0037] S3: Drying the precipitate to obtain a blend.

[0038] S4: Melting, hot pressing and isothermal crystallization of the blend to obtain a structure such as Figure 1 The high-strength and high-barrier polylactic acid film shown.

[0039] In a specific embodiment, the melting temperature is 230-240°C, the melting time is 4-5min; the hot pressing pressure is 20MPa, and the hot pressing time is 2-3min; the isothermal crystallization temperature is 120°C, the isothermal crystallization pressure is 15-20MPa, and the isothermal crystallization time is 0-30min.

[0040] In the present invention, the blend is only blended by mechanical stirring of the solution, which is simple and safe to operate, can be achieved in a relatively low temperature environment, and has low production cost. The amount of block copolymer polylactic acid used in the present invention is less than 5%, and the stereocomplex crystallization of a very small amount of block copolymer polylactic acid can promote the formation of homogeneous crystallization of left-handed or right-handed polylactic acid. The isothermal crystallization temperature is 120°C, the crystallization temperature is low, the crystallinity can reach 60%, and the crystallinity is high. In the preparation process of the polylactic acid film of the present invention, there are two kinds of stereocomplex effects, one is the stereocomplex effect between the left-handed and right-handed chains of the block copolymer polylactic acid itself; the other is the stereocomplex effect between the block copolymer polylactic acid and the left-handed or right-handed polylactic acid of the polylactic acid matrix, that is, the left-handed segment in the block copolymer polylactic acid and the right-handed segment in the matrix or the right-handed segment in the block copolymer polylactic acid and the left-handed segment in the matrix. The present invention can give the polylactic acid film high barrier properties and high mechanical properties while improving the crystallinity.

[0041] On the other hand, the present invention also provides a high-strength and high-barrier polylactic acid film prepared by any of the above-mentioned methods for preparing a high-strength and high-barrier polylactic acid film and its application in the field of packaging or agricultural mulch film.

[0042] Example 1

[0043] A high-strength and high-barrier polylactic acid film is prepared by the following steps:

[0044] (1) Weigh dextrorotatory polylactic acid (PDLA, M n =10.4×10 4 g / mol, PDI = 1.6) and block copolymer polylactic acid PLLA 50 -b-PDLA 50 In different beakers, dichloromethane was then added to each beaker and dissolved by mechanical stirring, and then the mixture was fully mixed according to the groups to obtain three groups of solutions.

[0045]

[0046] (2) The three groups of solutions are respectively dropped into a large amount of ethanol for precipitation to obtain three groups of precipitates.

[0047] (3) The three groups of precipitates were dried separately to obtain three dextrorotatory polylactic acid / block copolymer polylactic acid blends, which were named PDLA / LD50-1%, PDLA / LD50-3% and PDLA / LD50-5%, respectively.

[0048] (4) The three blends were melted, hot pressed and isothermally crystallized by a hot press to obtain high-strength and high-barrier polylactic acid films. The melting temperature was 230°C and the melting time was 5 min; the hot pressing pressure was 20 MPa and the hot pressing time was 3 min; the isothermal crystallization temperature was 120°C, the isothermal crystallization pressure was 20 MPa and the isothermal crystallization time was 10 min.

[0049] Example 2

[0050] A high-strength and high-barrier polylactic acid film is prepared by the following steps:

[0051] (1) Weigh the following table to weigh polylactic acid (PLLA, M n =12.7×10 4 g / mol, PDI = 1.5) and block copolymer polylactic acid PLLA 100 -b-PDLA 100 In different beakers, hexafluoroisopropanol was then added to each beaker and dissolved by mechanical stirring, and then the groups were fully mixed to obtain three groups of solutions.

[0052]

[0053] (2) The three groups of solutions are respectively dropped into a large amount of ethanol for precipitation to obtain three groups of precipitates.

[0054] (3) The three groups of precipitates were dried separately to obtain three L-polylactic acid / block copolymer polylactic acid blends, which were named PLLA / LD100-1%, PLLA / LD100-3% and PLLA / LD100-5%, respectively.

[0055] (4) The three blends were melted, hot pressed and isothermally crystallized by a hot press to obtain high-strength and high-barrier polylactic acid films. The melting temperature was 230°C and the melting time was 4 min; the hot pressing pressure was 20 MPa and the hot pressing time was 2 min; the isothermal crystallization temperature was 120°C and the isothermal crystallization pressure was 17 MPa. The three blends were isothermally crystallized for 0 min, 10 min, 20 min and 30 min respectively (the results of the three blend films at different isothermal crystallization times were recorded respectively).

[0056] Example 3

[0057] A high-strength and high-barrier polylactic acid film is prepared by the following steps:

[0058] (1) Weigh the following table to weigh polylactic acid (PLLA, M n =8.3×10 4g / mol, PDI = 1.1) and block copolymer polylactic acid PDLA 200 -b-PLLA 200 In different beakers, dichloromethane was then added to each beaker and dissolved by mechanical stirring, and then the mixture was fully mixed according to the groups to obtain three groups of solutions.

[0059]

[0060] (2) The three groups of solutions are respectively dropped into a large amount of ethanol for precipitation to obtain three groups of precipitates.

[0061] (3) The three groups of precipitates were dried separately to obtain three L-polylactic acid / block copolymer polylactic acid blends, which were named PLLA / DL200-1%, PLLA / DL200-3% and PLLA / DL200-5%, respectively.

[0062] (4) The three blends were melted, hot pressed and isothermally crystallized by a hot press to obtain high-strength and high-barrier polylactic acid films. The melting temperature was 240°C, the melting time was 4 min, the hot pressing pressure was 20 MPa, and the hot pressing time was 2 min. The isothermal crystallization temperature was 120°C, the isothermal crystallization pressure was 15 MPa, and the isothermal crystallization time was 0 min, 10 min, 20 min and 30 min (the results of the three blend films at different isothermal crystallization times were recorded respectively).

[0063] Example 4

[0064] A high-strength and high-barrier polylactic acid film is prepared by the following steps:

[0065] (1) Weigh the following table to weigh polylactic acid (PLLA, M n =16.1×10 4 g / mol, PDI = 1.8) and block copolymer polylactic acid PDLA 50 -b-PLLA 50 In different beakers, dichloromethane was then added to each beaker and dissolved by mechanical stirring, and then the mixture was fully mixed according to the groups to obtain three groups of solutions.

[0066]

[0067] (2) The three groups of solutions are respectively dropped into a large amount of ethanol for precipitation to obtain three groups of precipitates.

[0068] (3) The three groups of precipitates were dried separately to obtain three L-polylactic acid / block copolymer polylactic acid blends, which were named PLLA / DL50-1%, PLLA / DL50-3% and PLLA / DL50-5%, respectively.

[0069] (4) The three blends were melted, hot pressed and isothermally crystallized by a hot press to obtain high-strength and high-barrier polylactic acid films. The melting temperature was 235°C and the melting time was 4 min; the hot pressing pressure was 20 MPa and the hot pressing time was 3 min; the isothermal crystallization temperature was 120°C, the isothermal crystallization pressure was 18 MPa, and the isothermal crystallization time was 0 min, 10 min, 20 min and 30 min (the results of the three blend films at different isothermal crystallization times were recorded respectively).

[0070] Example 5

[0071] A high-strength and high-barrier polylactic acid film is prepared by the following steps:

[0072] (1) Weigh dextrorotatory polylactic acid (PDLA, M n =17.5×10 4 g / mol, PDI = 1.9) and block copolymer polylactic acid PDLA 100 -b-PLLA 100 In different beakers, hexafluoroisopropanol was then added to each beaker and dissolved by mechanical stirring, and then the groups were fully mixed to obtain three groups of solutions.

[0073]

[0074] (2) The three groups of solutions are respectively dropped into a large amount of ethanol for precipitation to obtain three groups of precipitates.

[0075] (3) The three groups of precipitates were dried separately to obtain three dextrorotatory polylactic acid / block copolymer polylactic acid blends, which were named PDLA / DL100-1%, PDLA / DL100-3% and PDLA / DL100-5%, respectively.

[0076] (4) The three blends were melted, hot pressed and isothermally crystallized by a hot press to obtain high-strength and high-barrier polylactic acid films. The melting temperature was 230°C and the melting time was 5 min; the hot pressing pressure was 20 MPa and the hot pressing time was 2 min; the isothermal crystallization temperature was 120°C, the isothermal crystallization pressure was 20 MPa, and the isothermal crystallization time was 0 min, 10 min, 20 min and 30 min (the results of the three blend films at different isothermal crystallization times were recorded respectively).

[0077] Example 6

[0078] A high-strength and high-barrier polylactic acid film is prepared by the following steps:

[0079] (1) Weigh dextrorotatory polylactic acid (PDLA, M n =14.8×10 4 g / mol, PDI = 1.5) and block copolymer polylactic acid PLLA 200 -b-PDLA 200 In different beakers, dichloromethane was then added to each beaker and dissolved by mechanical stirring, and then the mixture was fully mixed according to the groups to obtain three groups of solutions.

[0080]

[0081] (2) The three groups of solutions are respectively dropped into a large amount of ethanol for precipitation to obtain three groups of precipitates.

[0082] (3) The three groups of precipitates were dried separately to obtain three dextrorotatory polylactic acid / block copolymer polylactic acid blends, which were named PDLA / LD200-1%, PDLA / LD200-3% and PDLA / LD200-5%, respectively.

[0083] (4) The three blends were melted, hot pressed and isothermally crystallized by a hot press to obtain high-strength and high-barrier polylactic acid films. The melting temperature was 240°C and the melting time was 4 min; the hot pressing pressure was 20 MPa and the hot pressing time was 2 min; the isothermal crystallization temperature was 120°C, the isothermal crystallization pressure was 20 MPa, and the isothermal crystallization time was 0 min, 10 min, 20 min and 30 min (the results of the three blend films at different isothermal crystallization times were recorded respectively).

[0084] Performance Testing:

[0085] The crystallization process of the dextrorotatory polylactic acid / block copolymer polylactic acid film prepared in Example 1 under a polarizing microscope is shown in FIG. Figure 2 As shown. First, the film after isothermal crystallization for 10 minutes was placed on a hot stage, and the polarizing microscope was focused using the crystals produced in the film. Then, the focal length and magnification were kept unchanged, and the hot stage was quickly heated to 230°C and kept for 5 minutes to completely melt the film sample. Then, it was quickly cooled to 120°C and kept, and the crystallization of the sample was observed at different times. The results showed that the L-polylactic acid with block copolymer polylactic acid added had a faster crystallization rate than the L-polylactic acid without block copolymer polylactic acid added, and as the amount of block copolymer polylactic acid added increased, the L-polylactic acid appeared earlier in crystallization, and the crystallization was more complete at the same time.

[0086] XRD test was performed on the L-PLA / block copolymerized PLA films with different isothermal crystallization times prepared in Example 2, and then the crystallinity was obtained by fitting using Jadge 6.0 software. The oxygen and water vapor barrier properties of the films were tested according to the Chinese national standards GB / T 1038.1-2022 and GB / T 1037-2021, respectively, and the relationship between the oxygen permeability coefficient and the water vapor permeability coefficient of the film and the crystallinity was obtained. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It can be seen that with the increase of crystallinity, the oxygen permeability coefficient of the film increases from about 1.6×10 -14 cm 3 cm / (cm 2 ·s·Pa) dropped to about 0.5×10 -14 cm 3 cm / (cm 2 ·s·Pa), the water vapor permeability coefficient is about 8.0×10 -14 g·cm / (cm 2 ·s·Pa) dropped to about 3.0×10 -14 g·cm / (cm 2 ·s·Pa). The blend film prepared by the present invention has good oxygen and water vapor barrier properties. Compared with the method of adding nano barrier nucleating agent to polylactic acid in patent CN114410087A and adding organic and inorganic composite nucleating agent to polylactic acid in patent CN112708250A to promote polylactic acid crystallization and improve barrier properties, the oxygen permeability coefficient of the present invention is about 50% lower; compared with the method of adding stereopolymer polylactic acid nanosphere nucleating agent to polylactic acid in patent CN118388819A to promote polylactic acid crystallization and improve barrier properties, the water vapor permeability coefficient of the present invention is about 71% lower; compared with the method of adding composite antibacterial nucleating agent to polylactic acid in patent CN115449199A to promote polylactic acid crystallization and improve barrier properties, the water vapor permeability coefficient of the present invention is about 72% lower and the oxygen permeability coefficient is about 55% lower. In short, the barrier properties of the film prepared by the present invention are significantly better than the technical level reported in the prior art.

[0087] The tensile properties of the L-PLA / block copolymerized PLA film prepared in Example 3 were tested according to ASTM D882-10. As the isothermal crystallization time increased, the tensile strength and elongation at break of the film gradually decreased. Only the results of isothermal crystallization at 0 min (amorphous) and 30 min are shown here. Figure 5 and Figure 6 As shown. Figure 5 and Figure 6It can be seen that when the film is amorphous, the tensile strength and elongation at break are relatively high, while when the isothermal crystallization is 30 minutes, the tensile strength and elongation at break of the film are lower than those when the film is amorphous. However, whether it is amorphous or fully crystallized (crystallization for 30 minutes), the tensile strength of the film is always maintained at around 65MPa, and although the elongation at break has decreased, it is still maintained above 3%, and both show yield; while the tensile strength of pure left-handed polylactic acid drops to 45MPa after 30 minutes of isothermal crystallization, and the elongation at break drops to below 2.5%, and it shows brittleness. This shows that adding block copolymer polylactic acid can not only improve the crystallization behavior of polylactic acid and improve the barrier performance of polylactic acid, but also improve the tensile strength of polylactic acid, and reduce the rigidity of polylactic acid, making it have a certain flexibility.

[0088] The crystallinity changes of the polylactic acid film, pure PLLA film and pure PDLA film prepared in Examples 4-6 at different isothermal crystallization times are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that with the increase of block copolymer polylactic acid molecular weight and addition amount, the polylactic acid matrix can basically achieve complete crystallization within 20 minutes, with a crystallinity of about 60%, while the crystallinity of the polylactic acid matrix without block copolymer polylactic acid within 20 minutes is only 16%. In contrast, the addition of block copolymer polylactic acid can increase the crystallinity of the polylactic acid matrix by 275%. For pure PLLA film and pure PDLA film, adding block copolymer polylactic acid PLLA m -b-PDLA m or PDLA m -b-PLLA m Both can induce crystallization and improve crystallinity. The larger the molecular weight of block copolymer polylactic acid and the more it is added, the shorter the time it takes to achieve complete crystallization.

[0089] It should be noted that the above embodiments are only some embodiments of the present invention. 40 -b-PLLA 40 and PDLA 210 -b-PLLA 210 When preparing polylactic acid film, when the addition amount of block copolymer polylactic acid is 5%, the crystallinity of isothermal crystallization for 30 minutes is less than 50%. It is necessary to add a larger amount of nucleating agent to achieve results similar to those of Example 5 and Example 6, and the addition amount of block copolymer polylactic acid is too large to destroy the arrangement of the molecular chain of the polylactic acid matrix, resulting in a decrease in the performance of the polylactic acid material.

[0090] In summary, the present invention focuses on polylactic acid itself, and without introducing any other non-polylactic acid components, block copolymerization of polylactic acid promotes rapid crystallization of the polylactic acid matrix, improves crystallinity, and gives polylactic acid high barrier and high mechanical strength. Compared with the prior art, the present invention has significant progress.

[0091] The above descriptions are only representative embodiments of the present invention and are not intended to limit the present invention in any form. Any technician familiar with the profession who makes slight changes or modifications to the embodiments using the above disclosed technical contents without departing from the scope of the technical solution of the present invention are equivalent embodiments of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-strength and high-barrier polylactic acid film, characterized in that: The following steps are involved: S1: using a solvent to dissolve the polylactic acid matrix and the block copolymer polylactic acid respectively, and then mixing them to obtain a solution; S2: precipitating the solution through ethanol to obtain a precipitate; S3: drying the precipitate to obtain a blend; S4: melting, hot pressing and isothermal crystallization of the blend to obtain the high-strength and high-barrier polylactic acid film.

2. The method for preparing a high-strength and high-barrier polylactic acid film according to claim 1, characterized in that: In step S1, the solvent is dichloromethane and / or hexafluoroisopropanol.

3. The method for preparing a high-strength and high-barrier polylactic acid film according to claim 1, characterized in that: In step S1, the polylactic acid matrix is ​​left-handed polylactic acid or right-handed polylactic acid.

4. The method for preparing a high-strength and high-barrier polylactic acid film according to claim 1, characterized in that: In step S1, the average molecular weight M of the polylactic acid matrix is n Greater than or equal to 8×10 4 g / mol and less than or equal to 18×10 4 g / mol, and the polydispersity index PDI is greater than 1 and less than 2.

5. The method for preparing a high-strength and high-barrier polylactic acid film according to claim 1, characterized in that: In step S1, the block copolymer polylactic acid is PLLA m -b-PDLA m or PDLA m -b-PLLA m , where 50≤m≤200, and m is the degree of polymerization.

6. The method for preparing a high-strength and high-barrier polylactic acid film according to claim 1, characterized in that: In step S1, the block copolymerized polylactic acid accounts for 1-5% of the total mass of the polylactic acid matrix and the block copolymerized polylactic acid in terms of mass percentage.

7. The method for preparing a high-strength and high-barrier polylactic acid film according to any one of claims 1 to 6, characterized in that: In step S4, the melting temperature is 230-240°C, the melting time is 4-5 min; the hot pressing pressure is 20 MPa, and the hot pressing time is 2-3 min; the isothermal crystallization temperature is 120°C, the isothermal crystallization pressure is 15-20 MPa, and the isothermal crystallization time is 0-30 min.

8. A high-strength and high-barrier polylactic acid film, characterized in that: The high-strength and high-barrier polylactic acid film is prepared by the preparation method of any one of claims 1 to 7.

9. Use of the high-strength and high-barrier polylactic acid film as claimed in claim 8 in the field of packaging or agricultural mulch film.

Citation Information

Patent Citations

  • Rigid multi-amide nucleating agent for rapid crystallization of polylactic acid, and modified polylactic acid material

    CN103804864A

  • A macromolecular nucleating agent for rapid crystallization of polylactic acid and its application method

    CN110016133B

  • High-transparency and high-barrier polylactic acid material as well as preparation method and application thereof

    CN112708250A

  • Nucleating agent for polylactic acid and application method ofnucleating agent

    CN113025014A

  • A polylactic acid composition containing an amide-type nucleating agent and its preparation method

    CN113429768B